Analisis Kontrastif Majaz Bahasa Arab - Indonesia dan Implikasinya dalam Pembelajaran Ilmu Bayan - hilmi, danial (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Learning Bayan Science requires a comprehensive and comprehensive understanding because it relates to the way a person in understanding a person's text or speech. Understanding can not be achieved except by appreciation and inspiration to what is around the learner. Therefore, contrastive analysis can help the understanding of learners in understanding how important the comparison of language to facilitate the understanding of al-Qur'an al-Karim. This happens because the phrases contained in each instance are always related to the language style normally experienced by the learning itself. There are many similarities in the form of Arabic languages with Indonesia but the different categories and laying causes difficulties in studying Bayan. Through contrastive analysis, Bayan learning becomes more interesting and easier to understand.